Rising Powers and Multilateral Institutions - Lesage, Dries. author. aut Link
XXII, 298 p.
Keywords: The rise of new powers such as China and India is sending shockwaves through the global multilateral system. This volume systematically examines how 13 multilateral institutions are responding to this shift, with some deploying innovative outreach and reform activities, while others are paralyzed by gridlock or even retreat from the global scene.